Implementation Policy: Regional Tax Exemption from the Perspective of Boarding House Taxpayers - Rohmatunnisa, Layly Dwi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
This Study: This aims to understand and describe owners' perceptions. Boarding house businesses in Malang City towards the implementation of implementation policy of liberation of tax area business boarding house businesses. Research This is a qualitative study with the use interview method with nine owner boarding house businesses, Malang City Regional Revenue Agency officers, and one officer at the Malang Pratama Tax Office. Research results show that policy liberalization of tax boarding houses causes a different view: owner businesses feel benefited, while BAPENDA considers the lost government revenue​ becomes a mediator to evaluate policy. This is a balancing solution that burdens taxes and efficiency management income area.